مساهمة وسائل التواصل الاجتماعي في تطوير مدونات المثقفين العرب - جبلي,فاتح; دراوات,وحيد (University of Eloued جامعة الوادي, 2025)
سعينا من خلال هذه الورقة البحثية إلى الكشف عن عوامل تطوير مدونات المثقفين العرب من خلال وسائل الاتصال الحديثة، ورصد أبرز السبل لتحقيق ذلك بالاعتماد على الطريقة الاستقرائية في تتبع أبحاث المهتمين بشأن مجتمع المعلومات في الوطن العربي ونقدها، استنتج الباحثان بأن ولوج عالم المعرفة الرقمي يستوجب تعزيز التعاون بين المثقفين العرب من خلال المنصات الالكترونية المتاحة واستثمارها في إنتاج المعرفة ونشرها فيما بينهم؛ وعدم الاكتفاء باستهلاكها وتشويهها، والمشاركة عبر التفاعل بين المدونين والاستفادة من تجارب بعضهم البعض ونقلها فيما بينهم مما يرتقي بها ويحسنها باستمرار.Abstract: This research paper sought to identify factors for improving the blog posts of Arab intellectuals through modern communication media and monitor the most prominent ways to achieve that based on the inductive method of tracking research on the information society in the Arab world and criticizing them. The researcher concluded that entry into the field of digital knowledge requires a strengthening of co llaboration among Arab intellectuals through available electronic platforms and investing in them in the production and dissemination of knowledge among them, not just consumption and distortion of them and Participation through interaction between bloggers and by taking advantage of each other's experiences and transferring them to each other raises and continuously improves them).
Keywords: وسائل الاتصال الحديثة; مدونات، مثقف; مجتمع المعرفة; Modern communication media; Blogs; Intellectual; Information society